Correlates of gambling - Brochado, A.; Abreu, M.; Mendes, V. (Economics Bulletin, 2020)
This study's main objective was to identify which of gamblers' demographic, geographic and socioeconomic characteristics correlate with more frequent lottery playing and stock market trading. The data were collected from two unrelated cross-sectional samples of equity investors and lottery players from a European country. Based on a multiple correspondence analysis of both samples, higher levels of spending on central state lotteries and stocks with lottery features were found to be associated with individuals who have similar socioeconomic characteristics.